In situ studies of the degradation mechanisms of perovskite solar cells. Issue 2 (27th April 2020) - Kundu, Soumya; Kelly, Timothy L.
Abstract: The last decade has seen an extraordinary rise in the performance of perovskite solar cells (PSCs). State‐of‐the‐art devices now have efficiencies of over 25%, putting them on par with the best silicon solar cells. Yet despite their impressive performance, their longevity lags behind that of conventional silicon technology. Environmental factors like moisture, heat, and light can all adversely affect PSC performance and limit device lifetime. Systematically elucidating and eliminating PSC degradation pathways will be critical to the success of this technology. In situ techniques provide powerful tools to this end, as they allow structural, compositional, morphological, and optoelectronic changes to be tracked in real‐time. Because they follow a single film or device over the course of the degradation process, they can help eliminate the statistical variation that negatively affects many studies. Here we provide an overview of perovskite degradation processes, with an emphasis on in situ studies. Abstract : The lack of long‐term stability in perovskite solar cells is one of the greatest barriers to their commercialization. Here we review perovskite solar cell degradation mechanisms, with an emphasis on how in situ and operando methodologies have helped contribute to our understanding of these processes.